TARGET LEVELS OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM COMPONENTS AND THEIR ROLE IN CARDIOVASCULAR EVENT DEVELOPMENT AMONG PATIENTS WITH ARTERIAL HYPERTENSION - Sh. V. Akhadov; G. R. Ruzbanova; G. S. Molchanova; T. G. Talalaeva; S. N. Khoreva (Российский кардиологический журнал)
The aim of this study was to identify the optimal, characterised by minimal risk of cardiovascular events (CVE), levels of renin-angiotensin-aldosterone system (RAAS) components in patients with arterial hypertension (AH). In total, 454 patients with high-risk AH were examined (age 18-65 years; 92 men, 362 women). Plasma renin activity (PRA) and plasma aldosterone concentration (PAC) were assessed by radio-immune method, adrenalin and noradrenalin concentration in 24-hour urine sample – by fluorometric method, left ventricular myocardial structure and function – by echocardiography, renal function – by glomerular filtration rate (Reberg method) and 123 I-Hippuran renography. Target levels of RAAS components were defined as follows: PRA=0,22-3,0 ng/ml/h, if PAC: PRA=5-23 and PAC=0,18- 0,83 nmol/l (5-23 ng/dl). In patients with high CVE risk, the target levels of PRA=0,22-1,0 ng/ml/h and PAC: PRA=5-23 would minimize the risk of stroke, myocardial infarction, and target organ damage.